PENGARUH KOMITMEN ORGANISASI, PLURIFORM MOTIVASI DAN PARTISIPASI ANGGARAN PADA KINERJA MANAJERIAL PERUSAHAAN MANUFAKTUR DI JAWA TENGAH - Hariyanti, Widi; Siddiq, Faiz Rahman (Fakultas Ekonomi - Universitas Setia Budi, 2019)
This watchfulness was conducted to examine the effect organizational commitment, motivational pluriform, and budget participation on managerial performance, by using the unit analysis is manager who worked at the manufacturing company in Jawa Tengah. The sampling technique used is the purposive method, where the entire population sampled. Result from data processing, so can be taken conclusion as follows there positive influence and significant between variable organizational commitment, variable motivational pluriforn, and variable budget participation on managerial performance with significant and a significance value it can be concluded that the model is feasible research, and may explain the significant effect between variables organizational commitment, motivational pluriform, and budget participation are simultaneously on variable managerial performance. Result analysis of the coefficient determination indicates that the variables organizational commitment, motivational pluriform, and budget participation variation affecting the variable managerial performance.